Vertex Exponent of Asymmetric Two-coloured Cycle - Syahmarani, Aghni; Suwilo, Saib (Journal of Research in Mathematics Trends and Technology, 2020)
This paper is about an asymmetric two-coloured cycle. Let D be an asymmetric two-coloured cycle on n vertices, where n is odd and n >= 3, we show that the exponent of the k-th vertex of D is exactly (n2-1)/4 + ⌊ k/2 ⌋.